2003
DOI: 10.1097/00002030-200303070-00017
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and prevalence of HIV infection in pregnant Peruvian women

Abstract: HIV infection was related both to women's own risk behaviors and to the perceived risk behaviors of their sexual partners. Underlying societal factors related to heterosexual HIV infection, including deferral of marriage, warrant further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
31
0
10

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 7 publications
5
31
0
10
Order By: Relevance
“…In an analysis of pregnant women seeking care at the INMP in Lima, partner and partnership-related factors (perception of partner as a ''womanizer,'' partner history of illegal drug use) reported by a woman were strongly related to her HIV serostatus, independent of her own risk behaviors. 10 Another recent case-control study of HIVþ and HIVÀ women in Peru observed that partner risk behaviors, including sex with female sex workers (FSWs) or sex with other men, were the strongest predictors of HIV status, and that even monogamous women had extraordinarily large sexual networks due to partner behavior. 11 However, with the possible exception of short duration of current partnership, and ever using condoms, our results did not elucidate other partner and partnership-related factors associated with CT infection in this population.…”
Section: Discussionmentioning
confidence: 99%
“…In an analysis of pregnant women seeking care at the INMP in Lima, partner and partnership-related factors (perception of partner as a ''womanizer,'' partner history of illegal drug use) reported by a woman were strongly related to her HIV serostatus, independent of her own risk behaviors. 10 Another recent case-control study of HIVþ and HIVÀ women in Peru observed that partner risk behaviors, including sex with female sex workers (FSWs) or sex with other men, were the strongest predictors of HIV status, and that even monogamous women had extraordinarily large sexual networks due to partner behavior. 11 However, with the possible exception of short duration of current partnership, and ever using condoms, our results did not elucidate other partner and partnership-related factors associated with CT infection in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the male partners of these HIV positive pregnant women, who were also HIV positive, were more likely to have used illegal drugs [25]. Alcohol intoxication at least once per month and illegal drug use were associated with increased risk of acquiring HIV in another group of pregnant women in Lima [26]. The importance of women partner's sexual network was highlighted by the finding that the likelihood of being HIV positive increased when a woman's sexual partner either had AIDS, used illegal drugs or alcohol, used intravenous drugs, or had sex with men [26].…”
Section: Evidence Of the Association Between Substance Use And Hiv Trmentioning
confidence: 96%
“…Se estima que la transmisión sexual ocurre en el 97% de los casos, estando la epidemia concentrada en hombres que tienen sexo con hombres (HSH) (2)(3)(4)(5)(6) . Alrededor de la mitad de los HSH encuestados en estudios previos refirió tener relaciones sexuales también con mujeres, y el grupo reportó bajo uso de condón en todas sus relaciones (3)(4)(5)(6) . A nivel mundial, hasta 80% de las mujeres infectadas se contagiaron de su esposo o pareja estable (7) .…”
Section: Artículo Originalunclassified